Exploring risk associated to public road infrastructure construction projects - Razi, P. Z.; Mohamad Idris, Ali; Noram Irwan, Ramli (IOP Publishing Ltd., 2021)
This study proposed an empirical study of risk assessment module for public road infrastructure construction projects. This study employs a case study of a public road infrastructure construction projects located at a state in East Coast of Malaysia. The projects involve the construction of new four (4) lane road along 5.875km aligned from the state route to federal route. The project will be benefited to the federal and state economic development, while for the local residents, they will benefited with reducing of traffic congestion. However, due to several uncertainties, schedule delays have occurred to the particular area. Thus, this study conducted to explore the risk associated with the project, and four delay factors and thirteen sub-factors have emerged prior to the consultations with project team experts. The delay risk assessed quantitatively employing the Analytic Hierarchy Process (AHP) technique by prioritising the risk delay factors. Design of the AHP model and the operation of the pair-wise rating was employed the super-decision software. The analysis revealed that when considering all factor concerning the goal, the project risk (0.348) captured the most prioritised risk factor that caused by land acquisition issues (0.555), followed by environmental (0.233) caused by the uncertainty of weather (0.733), operational risk (0.309) caused by late submission of approved for construction drawing causing a delay in projects submission delay (0.396) as the last prioritised risk factors in the construction project and technical risk (0.110) caused by the new design does not consider existing drainage system causing flood (0.352). Findings of this study will beneficial to the project team, as the prioritised risk will act as their references and guidance to avoid delays and incurring of project costs.